2022
DOI: 10.1021/acsnano.1c09388
|View full text |Cite
|
Sign up to set email alerts
|

Self-Bonded Hydrogel Inverse Opal Particles as Sprayed Flexible Patch for Wound Healing

Abstract: Wound healing is an important issue for regenerative medicine. Attempts in this area tend to develop functional wound patches to promote the healing. Here, we present self-bonded hydrogel inverse opal particles as sprayed flexible patch for wound healing. Such particles were fabricated by infusing drugs-loaded gelatin (GT) and carrageenan (CG) pregel into inverse opal scaffolds, which were composed of biocompatible hyaluronic acid methacryloyl (HAMA) and gelatin methacryloyl (GelMA) with graphene oxide quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…Y-DNA showed a positive effect on wound healing, which may be attributed to the good biocompatibility and antioxidant capacity of DNA. , Masson staining was used to observe the collagen formation (blue) during wound healing (Figure e). Collagen plays a significant role in the proliferation and differentiation of tissue cells, regarded as an important indicator for skin tissue reconstruction and wound repair . The images showed that the collagen fiber deposition in three groups on day 5 was lower than that on day 15.…”
Section: Resultsmentioning
confidence: 95%
“…Y-DNA showed a positive effect on wound healing, which may be attributed to the good biocompatibility and antioxidant capacity of DNA. , Masson staining was used to observe the collagen formation (blue) during wound healing (Figure e). Collagen plays a significant role in the proliferation and differentiation of tissue cells, regarded as an important indicator for skin tissue reconstruction and wound repair . The images showed that the collagen fiber deposition in three groups on day 5 was lower than that on day 15.…”
Section: Resultsmentioning
confidence: 95%
“…[53][54][55][56] Due to the lack of adhesive action, excessive swelling, and premature degradation upon contact with tissue, the mechanical properties of HA-based hydrogels are generally poor as wound repairing materials. These issues can be addressed by chemical modification of HA to improve the cross-linking degree of networks, and the interpenetration and entanglement of the polymer chains, including catechol [57][58][59][60][61][62][63] and pyrogallol 57,64 for musselinspired catechol chemistry through hydrogen-bond interaction and metal ions coordination, aldehydes from periodate oxidation of HA 60,[65][66][67][68][69] and photoactive o-nitrobenzyl [70][71][72][73] for Schiff base reaction, methacrylate 61,62,71,[74][75][76] for photoinitiated free radical polymerization, phenylboronic acid 77,78 for glucose-sensitive dynamic borate bond with polyphenol groups, etc.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…84,86,[128][129][130] In addition, catechol [130][131][132][133][134] /pyrogallol [135][136][137] are introduced into gelatinbased hydrogels for further adhesion enhancement, and methacrylate gelatin (GelMA) hydrogels are preferred for convenience in some cases. 76,126,134,[138][139][140][141] Building on the above methods, researchers have recently developed a series of excellent wound management strategies. For example, Huang et al 139 designed an octopus suction cup-mimicking wound patch with selective adhesive property and individualized design possibility (Fig.…”
Section: Collagen and Gelatinmentioning
confidence: 99%
See 1 more Smart Citation
“…For drug delivery, HAMA–GelMA composite hydrogels doped with graphene oxide quantum dots (GO-QDs) were constructed as a drug delivery system, and the photothermal conversion capability of GO-QDs gave the scaffold the ability to guide wound tissue healing and drug delivery monitoring. 144 Whereas Pluronic F127 diacrylate (F127DA) nano micelles enhance the compressive properties of HAMA hydrogels and exhibit low swelling ratios, effectively promoting cartilage regeneration in vivo , 66 this multiscale delivery system based on HAMA with ready-to-use particles is expected to be an excellent strategy for regenerative IVD.…”
Section: Stimulus-responsive Composite Hydrogelsmentioning
confidence: 99%